2013
DOI: 10.3354/ame01643
|View full text |Cite
|
Sign up to set email alerts
|

Global-scale distributions of marine surface bacterioplankton groups along gradients of salinity, temperature, and chlorophyll: a meta-analysis of fluorescence in situ hybridization studies

Abstract: We used literature data on marine bacterial (sub)group abundances, as determined by fluorescence in situ hybridization, to test whether the ecological variability of the different subgroups was similar to that of the bacterial community as a whole. Patterns of 6 major groups are described (Alpha-, Beta-, Gammaproteobacteria and Bacteroidetes, as well as Rhodobacteraceae and SAR11) and related to environmental variables such as chlorophyll a (chl a) concentration, salinity, and temperature, distinguishing betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 101 publications
6
25
0
2
Order By: Relevance
“…Marine waters are dominated by Alpha - and Gammaproteobacteria , and limnetic areas by Actinobacteria and Betaproteobacteria (Kirchman et al, 2005; Logares et al, 2009; Lefort and Gasol, 2013). The typical abundance shift of Cyanobacteria as well as changes in bacterial community composition and richness between July and February were also observed in this study (Fuhrman et al, 2008; Fortunato and Crump, 2015), with the dataset showing that both salinity-related and seasonal differences caused phylogenetically clustered shifts in bacterial community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Marine waters are dominated by Alpha - and Gammaproteobacteria , and limnetic areas by Actinobacteria and Betaproteobacteria (Kirchman et al, 2005; Logares et al, 2009; Lefort and Gasol, 2013). The typical abundance shift of Cyanobacteria as well as changes in bacterial community composition and richness between July and February were also observed in this study (Fuhrman et al, 2008; Fortunato and Crump, 2015), with the dataset showing that both salinity-related and seasonal differences caused phylogenetically clustered shifts in bacterial community composition.…”
Section: Discussionmentioning
confidence: 99%
“…The stable phylogenetic lineages of the "Pelagibacterales" exhibit distinct spatio-temporal abundance patterns in the water column [5,16,[20][21][22]]. An amplicon sequencing study of samples from the Baltic Sea demonstrated shifts in the relative abundance of amplicon sequencing reads from subclade SAR11-I to subclade SAR-IIIa in the transition from marine to oligohaline conditions [12].…”
Section: Introductionmentioning
confidence: 98%
“…Bacteroidetes is a cosmopolitan phylum that typically constitutes between 4 and 22% of marine bacterioplankton cells (Glöckner et al, 1999; Cottrell and Kirchman, 2000; Alonso-Sáez et al, 2007; Ruiz-González et al, 2012; Lefort and Gasol, 2013; Acinas et al, 2014). The relative abundance of Bacteroidetes can reach up to 53% and it often correlates with phytoplankton blooms (Abell and Bowman, 2005; Fandino et al, 2005).…”
Section: Introductionmentioning
confidence: 99%